Corrosion Characterization of TiO2 Particulate Reinforced Al-6063 Composites in Chloride and Nitrate Media - Bheema Raju, V.; Ananda Murthy, H.C.; Sanaulla, P.F. (Asian Journal of Chemistry, 2010)
The corrosion behaviour of Al 6063-TiO2 particulate composites in chloride and nitrate media has been studied in the present investigation. The unreinforced matrix and the composites containing 2, 4 and 6 % by weight of TiO2 particulates were prepared by liquid metallurgy route using vortex technique. The potentiodynamic polarization experiments revealed that the composites are susceptible to corrosion compared with their matrix alloy. Moreover, the corrosion rates of the composites markedly increases with increase in the TiO2 content. The pitting effect was more pronounced in presence of aggressive Cl– ions compared to mild NO3 – ions. The observed lower corrosion resistance in composites could be attributed to the microgalvanic coupling between the intermetallics around the reinforcement particles such as Mg2Si, AlTi3 and matrix alloy. Insulator TiO2 particulates are perceived to act as inert material and degrade the integrity of the protective oxide layer on the Al matrix alloy. SEM and EDX analysis of samples in chloride media showed the presence of large pits and completely deteriorated surface, complementing polarization studies.